Differences in responses to English and Korean versions of the Caregiver Priorities & Child Health Index of Life with Disabilities (CPCHILD) - Sung, Ki Hyuk; Kwon, Soon Sun; Cho, Gyeong Hee; Chung, Chin Youb; Encisa, Clarissa; Menal, Huroy; Narayanan, Unni G.; Park, Moon Seok (Health and Quality of Life Outcomes, 2020)
Background: The purpose of this study was to identify differences in caregiver responses to Korean-language and English-language versions of the Caregiver Priorities & Child Health Index of Life with Disabilities (CPCHILD) questionnaire. Methods: Patient data were acquired from the Cerebral Palsy Hip Outcomes Project database, which was established to run a large international multicenter prospective cohort study of the outcomes of hip interventions in cerebral palsy. Thirty-three children whose caregivers had completed the Korean version of CPCHILD were matched by propensity scoring with 33 children whose parents completed the English version. Matching was performed on the basis of 12 covariates: age, gender, gross motor function classification system level, migration percentage of right and hip, seizure status, feeding method, tracheostomy status, pelvic obliquity, spinal deformity, parental report of hip pain and contracture interfering with care. Results: There were no significant differences in CPCHILD scores for section 4 (Communication and Social Interaction), and section 5 (Health) between two groups. Korean-language CPCHILD scores were significantly lower than English-language CPCHILD scores for section 1 (Personal Care/Activities of Daily Living), section 2 (Positioning, Transferring and Mobility), section 3 (Comfort and Emotions) and section 6 (Overall Quality of Life) as well as in terms of total score. Conclusions: Cultural influences, and the community or social environment may impact the caregivers' perception of the health-related quality of life of their children. Therefore, physicians should consider these differences when interpreting the study outcomes across different countries.
Keywords: Adolescent; Adult; Caregivers; Cerebral Palsy; Child; Child, Preschool; Cross-Cultural Comparison; Disabled Persons; Female; Humans; Language; Male; Middle Aged; Parents; Prospective Studies; Quality of Life; Republic of Korea; Surveys and Questionnaires; Cerebral palsy; English; Korean; Questionnaire; Social environment